Wrinkles Profile In Various Age And Gender Using Visia® Imaging In Indonesia: A Single-Center Study - Arini Astasari Widodo; Shifa Nurzahra Zaki; Angelina Wijaya (Universitas Pahlawan Tuanku Tambusai, 2025)
Introduction: Skin is the most recognizable manifestation of tissue aging, particularly the face, which is sensitive to skin aging due to frequent and extensive exposure to sunlight. Visible signs of facial aging, such as wrinkles, are common concerns among all ages, significantly impacting cosmetic appearance and often leading to negative psychological, emotional, and social consequences. Understanding wrinkle variations across age and gender is crucial for effective dermatological treatment and development of more personalized skincare regimens. This study aimed to describe and analyze wrinkles profile using VISIA® imaging technology across different age groups and genders. Methods: This analytic quantitative study with a cross-sectional design approach utilized medical records of registered patients at Dermalogia Clinic in Jakarta who underwent VISIA® imaging from 2024-2025. Wrinkles were assessed using VISIA® imaging system, which provides high-resolution, objective skin assessments through an automated quantified software, with depth and density metrics quantified using pixel-based algorithm. Wrinkle severity was quantitatively compared across age groups and genders. Results: Among 420 patients, wrinkle significantly worsen progressively with age (p<0.05), especially under the eyes and at crow's feet. Men aged 30-50 showed more pronounced wrinkles, with the >50 age group having the highest severity. Males exhibited deeper wrinkles than females, likely due to biological, hormonal, and environmental differences. Conclusion: Age and gender significantly influence facial wrinkle severity. VISIA® imaging provides a reliable objective assessment on skin aging, supporting personalized anti-aging treatments. Further studies are needed to explore lifestyle factors affecting wrinkle formation.